2022
DOI: 10.3390/cancers14061532
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of miR-125b, miR-200c and miR-205 in Primary Cutaneous Malignant Melanoma Is Independent of BRAF Mutational Status

Abstract: BRAF mutations are present in around 50% of cutaneous malignant melanomas and are related to a poor outcome in advanced-stage melanoma patients. miRNAs are epigenetic regulators that modulate different cellular processes in cancer, including melanoma development and progression. However, there are no studies on the potential associations of the genetic alterations of the BRAF gene with miRNA expression in primary cutaneous melanomas. Here, in order to analyze the influence of BRAF mutations in the ability of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It is known that the tumor invasion is the cancer progression, associated with the intracellular signaling, transcription and growth factors changes [ 12 , 37 , 65 ] and reflected in the aggressive tumor behavior. In addition, a high hsa-miR-125b expression was associated with the BRAF V600E status, which was disclosed in the results of the experiment on melanoma in cell culture [ 17 ]. The study showed an association between the cancer mutational status and hsa-miR-125b expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the tumor invasion is the cancer progression, associated with the intracellular signaling, transcription and growth factors changes [ 12 , 37 , 65 ] and reflected in the aggressive tumor behavior. In addition, a high hsa-miR-125b expression was associated with the BRAF V600E status, which was disclosed in the results of the experiment on melanoma in cell culture [ 17 ]. The study showed an association between the cancer mutational status and hsa-miR-125b expression.…”
Section: Discussionmentioning
confidence: 99%
“…An association between the miRNA’s rate and the BRAFV600E mutational status was found. It is a significant indicator of the aggressive PTC phenotype [ 17 ].…”
Section: Introductionmentioning
confidence: 99%